Towards zero rate in healthcare-associated infections: one size shall not fit all... - Lisboa, Thiago (BioMed Central, 2013)
ICU patients are identified as targets for quality of care and patient safety improvement strategies. Critically ill patients are at high risk for complications due to the complex and invasive nature of critical care. Several reports in the literature describe initiatives aiming to zero the healthcare-associated infection rate. We discuss the results of a study assessing a systematic team approach with very aggressive interventions surrounding the Institute for Healthcare Improvement Central Line-associated Blood Stream Infection bundle, which obtained a successful reduction of the rates. In addition, we discuss why some healthcare-associated infections are not fully preventable and the different reasons for this, the identification of which would be a cornerstone of quality improvement and safety promotion initiatives in critically ill patients.